Refleksja z katedry - Bukojemski, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Reflections from the Rostrum In his polemics with the Documentary Filmmaker Guide by Grażyna Kędzielawska, Michał Bukojemski claims that the notional apparatus, filmmaking methods, and production technologies described in the book do not adhere to the digital present day. The author believes that the teaching of documentary filmmaking in film school should begin with setting and describing the main goal, which is the film itself. Today’s documentary film has specific conditions, such as financing, distribution and shooting technologies. Speaking about various methods and practicing different forms of filmmaking are rather auxiliary goals that should be fulfilled in the course of studies. The author convinces us that both the subject and the story are crucial for the documentary film. And with them academic teachers should begin and end their teaching of documentary filmmaking.